Some Remarks on Fuzzy R0, R1 and Regular Topological Spaces - Ali, D. M.; Azam, F. A. (Journal of Scientific Research, 2012)
In this paper, five regular-axioms, eighteen -axioms and nine -axioms for fuzzy topological spaces are recalled. A complete answer is given with regard to all possible -type implications for fuzzy topological spaces. It is also shown that, though the regular-axiom implies -axiom in general topological spaces, this is not true for fuzzy topological spaces, in general. Keywords: Fuzzy Topological Space; Fuzzy -axiom; Fuzzy -axiom; Fuzzy regular axiom. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i2.6663 J. Sci. Res. 4 (2), 327-336 (2012)